The Effect Of A Virtually Generated, Traversable Environment On The Brain Regions Of Stress Of The University Students - Omirbayev, Sultan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
For mental health interventions, virtual reality (VR) presents exciting new modalities, especially for stress reduction in populations with limited access to natural settings. In this study, university students’ stress-related EEG markers are examined to determine the neurophysiological effects of a fully navigable, procedurally generated virtual nature environment. The EEG signals of eight participants, four men and four women, were recorded prior to and after two VR exposure sessions using an experimental design within the subject. Alpha power, theta power, frontal alpha asymmetry, theta/alpha ratio, and frontal midline theta were all important stress-related indicators that were extracted using a complete EEG preprocessing pipeline that included ICA and several filtering stages. Although statistically significant differences were not found by the paired t-tests, small to moderate effect sizes were observed in a number of domains, indicating possible trends. Interestingly, the mean theta power showed a slight increase after exposure, suggesting increased cognitive relaxation and potential memory involvement, while the mean alpha power remained constant. This pilot study establishes the foundation for scalable, non- pharmacological interventions in student mental health and shows that immersive virtual reality and EEG-based stress analysis are feasible. To confirm and build on these findings, more studies with larger sample sizes and longer exposure times are necessary.
Keywords: VR; BCI; EEG; Virtually Generated Environment; type of access: open access; PQDT_Master